Effect of antifungal agents on lipid biosynthesis and membrane integrity in Candida albicans. - Georgopapadakou, N H (1987)
Eight antifungal agents were examined for effects on lipid biosynthesis and membrane integrity in Candida albicans. Lipids were labeled in vivo or in vitro with [14C]acetate and analyzed by thin-layer and gas chromatography. Membrane integrity was measured by a recently developed [14C]aminoisobutyric acid radiolabel release assay. The imidazole antifungal agents miconazole, econazole, clotrimazole, and ketoconazole, at concentrations inhibiting ergosterol biosynthesis (0.1 microM), decreased the ratio of unsaturated to saturated fatty acids in vivo but not in vitro. Similarly, naftifine, tolnaftate, and the azasterol A25822B, at concentrations inhibiting ergosterol biosynthesis (10, 100, and 1 microM, respectively), decreased the ratio of unsaturated to saturated fatty acids in vivo only. This suggests that the effect on fatty acids observed with ergosterol biosynthesis inhibitors may be secondary to the effect on ergosterol. With imidazoles, oleic acid antagonized inhibition of cell growth but not inhibition of ergosterol. This suggests that, with the C-14 demethylase inhibitors, decreased unsaturated fatty acids, rather than decreased ergosterol, are responsible for growth inhibition. Cerulenin, previously reported to be a potent inhibitor of both fatty acid and ergosterol biosynthesis, was found in the present study to inhibit the former (at 5 microM) but not the latter (up to 100 microM). Of the antifungal agents tested, econazole and miconazole (at 100 microM) produced complete release of [14C]aminoisobutyric acid, which is consistent with membrane damage.